2017
DOI: 10.1002/ejlt.201700373
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Candida rugosa Lipase on Glutaraldehyde‐Activated Fe3O4@Chitosan as a Magnetically Separable Catalyst for Hydrolysis of Castor Oil

Abstract: In this study, the catalyzed hydrolysis of castor oil by Candida rugosa lipase (CRL) immobilized on glutaraldehyde‐activated magnetic Fe3O4@chitosan is investigated. Magnetic Fe3O4 is prepared by hydrothermal method and coated with chitosan (CS). Next, CRL is immobilized on Fe3O4@chitosan using glutaraldehyde as a cross‐linking reagent. The prepared Fe3O4@CS@CRL is confirmed by scanning electron microscopy (SEM), X‐ray powder diffraction (XRD), vibrating sample magnetometry (VSM), Fourier transform infrared (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For example, commercial CRL hydrolyzes butter oil in the absence of organic solvents and showed higher specificity toward butyric acid relative to Pseudomonas fluorescein lipase after 3 h of hydrolysis at 40 °C (22 vs 8 mol %, respectively) rendering it an ideal choice for a biological catalyst to generate useful dairy flavor profiles . Furthermore, immobilized CRL has been used for the enrichment of the production of omega-3 polyunsaturated fatty acids (eicosapentaenoic acid and docosahexaenoic acid) through hydrolysis of fish oil , or the hydrolysis of different plant oils to produce linoleic acid (LA), used as a flavor precursor, e.g., castor oil (conversion of 47%), safflower oil (conversion of 84%) and borage oil (conversion of 46%) …”
Section: Current and Promising (Industrial) Applicationsmentioning
confidence: 99%
“…For example, commercial CRL hydrolyzes butter oil in the absence of organic solvents and showed higher specificity toward butyric acid relative to Pseudomonas fluorescein lipase after 3 h of hydrolysis at 40 °C (22 vs 8 mol %, respectively) rendering it an ideal choice for a biological catalyst to generate useful dairy flavor profiles . Furthermore, immobilized CRL has been used for the enrichment of the production of omega-3 polyunsaturated fatty acids (eicosapentaenoic acid and docosahexaenoic acid) through hydrolysis of fish oil , or the hydrolysis of different plant oils to produce linoleic acid (LA), used as a flavor precursor, e.g., castor oil (conversion of 47%), safflower oil (conversion of 84%) and borage oil (conversion of 46%) …”
Section: Current and Promising (Industrial) Applicationsmentioning
confidence: 99%
“…The synthesis of supports Fe 3 O 4 -CS, Fe 3 O 4 -CS-GA, and Fe 3 O 4 -CS-DAC were referred to the previously reported literature with a minor modification ( Kim et al, 2017 ; Zhao et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The coating of magnetic nanoparticles with biopolymers like chitosan protects them against erosion and provides appropriate functional groups [14]. For example, magnetic Fe 3 O 4 nanoparticles were prepared by the hydrothermal method and coated with chitosan activated with glutaraldehyde and then used to immobilize CRL [66]. The biocatalyst was used to hydrolyze castor oil, with a degree of hydrolysis of 46% being obtained in 60 h at 34 • C. The activity was not stable: in the fourth hydrolysis cycle, the degree of hydrolysis was only 30%.…”
Section: Chitosanmentioning
confidence: 99%
“…The biocatalyst was used to hydrolyze castor oil, with a degree of hydrolysis of 46% being obtained in 60 h at 34 • C. The activity was not stable: in the fourth hydrolysis cycle, the degree of hydrolysis was only 30%. The authors suggested that the loss of activity was due to "irreversible" adsorption of substrate and product on the support, since they washed the biocatalyst with tertiary butyl alcohol and PBS (phosphate-buffered saline 0.02 M, pH 7.0) to remove any substrate or product that had been retained on the support [66].…”
Section: Chitosanmentioning
confidence: 99%